Komentarz do przekładów literatury polskiej na język macedoński w 2014 roku - Tanuševska, Lidija (Przekłady Literatur Słowiańskich, 2015)
Commentary on translations in Macedonian language, published in 2014 This commentary conserns the reasons and motivation for choosing particular novels to be translated into Macedonian. A short review of their style is given, as well as the common ground with the Macedonian literature. We describe the way of the working of the publishing houses which have decided to publish Polish literature. Problems in translation turn out to be of a cultural nature, concerning the differences and, as a result, the reader is presented with the picture of contemporary Polish society, which is overwhelmed by critical thinking, but still deals with the history as a way to further develop the tradition. Key words: novels, publishers, translating, colloquialisms